Rapid and sensitive analytical method for the determination of insulin in liposomes by reversed-phase HPLC - de Souza Von Zuben, Eliete [UNESP]; Eloy, Josimar Oliveira; Sousa Araujo, Victor Hugo [UNESP]; Daflon Gremião, Maria Palmira [UNESP]; Chorilli, Marlus [UNESP] (Slovenian Chemical Society, 2020)
Insulin is an important anabolic hormone that regulates the metabolism of carbohydrates, lipids and proteins. In this study, a reverse-phase liquid chromatography (RP-LC) method was successfully validated and tested for the encapsulation efficiency assay of insulin and in vitro release studies. HPLC analyses were carried out using a RP C18- Luna® Phenomenex (4.6 × 250 mm, 5 μm particle size) column maintained at room temperature, using a mobile phase constituted by a mixture of acetonitrile and 0.1% TFA aqueous solution (60:40, v/v), in an isocratic mode with a flow rate of 1.0 mL/ min, with ultraviolet detection at 214 nm and 20 μL of injection volume. Method validation was performed according recognized guidelines for system suitability, specificity, linearity, precision, accuracy, LOD, LOQ and robustness. The method was shown to be linear in the range of 0.5–100 µg/mL (r2 = 0.9993) selective, precise, robust, accurate with LOD and LOQ values were 0.097 µg/mL and 0.294 µg/mL, respectively. The developed method proved to be adequate to analyze the encapsulation efficiency and the profile of insulin release from liposomes.
Keywords: Encapsulation Efficiency; In Vitro Release; Insulin; Liposome; Liquid Chromatography; Validation Method